2009
DOI: 10.2106/jbjs.h.00416
|View full text |Cite
|
Sign up to set email alerts
|

Chondrosarcoma in the United States (1973 to 2003): An Analysis of 2890 Cases from the SEER Database

Abstract: Only grade and stage are independent prognostic factors for survival in cases of chondrosarcoma. Current treatment algorithms have not improved the survival rates of patients with chondrosarcoma over the past thirty years. Routine patient surveillance following treatment should be extended to ten years of follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

33
254
7
9

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 317 publications
(303 citation statements)
references
References 26 publications
33
254
7
9
Order By: Relevance
“…These limitations limit our ability to state which factors are the most important determinants of prognosis in this disease. Previous investigations into the prognostic factors associated with conventional chondrosarcoma have identified that histologic grade and margin status have been directly related to patient survival [9]. Neither histologic grade nor margin status was uniformly reported in this patient cohort.…”
Section: Discussionmentioning
confidence: 58%
See 3 more Smart Citations
“…These limitations limit our ability to state which factors are the most important determinants of prognosis in this disease. Previous investigations into the prognostic factors associated with conventional chondrosarcoma have identified that histologic grade and margin status have been directly related to patient survival [9]. Neither histologic grade nor margin status was uniformly reported in this patient cohort.…”
Section: Discussionmentioning
confidence: 58%
“…Survival by anatomic location of chondrosarcoma overall has been examined by Giuffrida et al [9]; however, subgroup analysis for mesenchymal chondrosarcoma was not performed. Consistent with previous data, patients with tumors affecting craniofacial sites were found to have a more favorable prognosis [4,16,23].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite improvements in diagnostic modalities and surgical techniques, there has not been an improvement in survival of patients with chondrosarcoma over the past 30 years, according to an analysis of US National Cancer Institute's Surveillance, Epidemiology, and End Results (SEER) data [7]. To improve the outcome of patients, it seems important to determine how to optimize the treatment of patients who develop recurrence of disease.…”
Section: Introductionmentioning
confidence: 99%